Pendampingan dan Transfer Teknologi Pengembangan Padi Sawah di Desa Pangelak, Kalimantan Selatan - Eka Maulidiya, Sherly; Junaedi, Ahmad; Purwono, Purwono; Suhartanto, Mohamad Rahmad; Wiyono, Suryo; Khairani, Khairani; Cahyani, Gesa Nur; Fitriansyah, Muhammad Ramdhani; Putri, Lystiana Dewi; Fadillah, Arvin Muhammad (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2024)
The agricultural technology transfer and mentoring program in Pangelak Village, South Kalimantan, aims to improve the efficiency and productivity of paddy rice cultivation through the application of appropriate technology and environmentally friendly cultivation practices. This activity involved 4 active IPB students, 1 person as project manager, 1 person as supervisor, and 4 IPB lecturers. The mentoring implementation method consists of preparation, program implementation, and evaluation. The program implementation stage begins with preparation, which includes field surveys and FGDs to understand the needs and conditions of the community. The next stage is assistance and technology transfer, which includes assistance in paddy rice cultivation, bioimmunization of seeds, and making organic plant ingredients as alternative fertilizers. The evaluation stage includes conducting interviews and discussions with farmers after the mentoring and technology transfer activities. The creation of IPB 3S demonstration plots was carried out in the context of innovation adoption through training and direct practice to farmers on more efficient cultivation techniques and the use of organic fertilizers. The mentoring program can increase knowledge and skills on effective and efficient cultivation techniques to farmers, introduce the latest technologies and innovations in rice cultivation, increase the productivity of paddy rice and the welfare of farmers.